Utilization of Malmath ICT-Based Learning Tools on Student Learning Outcomes - Yulia Utami; Desi Vinsensia; Awaludin Fitra (Peneliti.net, 2020)
The aimed of this reseacrh was to find the effect of using the malmath application learning media on learning outcomes on the subject of boundaries for 1st semester students of the Departement of Informatics. The population in this research were 1st semester students of Informatics Departemen. The sample consists of two classes taken randomly. One class is used as an experimental class with the use of malmath application learning media called class TI batch 1 the other class is a control class with conventional methods, called class TI batch 5. The data instument used for 5 validated quations. The data analysis used was the t-test. The findings of this research are as follows: (1) student learning outcomes in the experimental class using malmath aplication learning media obtained an average value (X) = 79,34 and standard deviation (s) = 13,59, (2) studen learning outcomes in the conventional class using only conventional methods, the average value is obtained (X) = 64,44 and standart deviation (s)19,17. Thats means the student learning outcomes in the experimental class are better than those in the control class. Hypothesis testing show that tcount = -2,9127 dan ttable = 2,0227, for α = 0,05 so that , from the t test results it is found that tcount is outside the ttable interval, it is realized that there is an effect the utilization of learning media for the malmath application on learning outcomes of STMIK Pelita Nusantara Medan students